2010
DOI: 10.1073/pnas.1014378107
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated immunity provides strong protection against the negative-strand RNA vesicular stomatitis virus in Drosophila

Abstract: Activation of innate antiviral responses in multicellular organisms relies on the recognition of structural differences between viral and cellular RNAs. Double-stranded (ds)RNA, produced during viral replication, is a well-known activator of antiviral defenses and triggers interferon production in vertebrates and RNAi in invertebrates and plants. Previous work in mammalian cells indicates that negative-strand RNA viruses do not appear to generate dsRNA, and that activation of innate immunity is triggered by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
134
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 47 publications
(40 reference statements)
18
134
1
3
Order By: Relevance
“…In contrast to the sharp 21-nt peak in WT flies and AGO2 mutants, small RNAs in Dcr-2 mutants showed a broader size distribution, with only a minor enrichment at 21 nt. A similar shift toward small RNAs with sizes other than 21 nt was noted before in Dcr-2 mutant flies infected with vesicular stomatitis virus (14). Recombinant and immunoprecipitated Dicer-1 (Dcr-1) is able to process long dsRNA into siRNA in in vitro assays, albeit with low efficiency (39)(40)(41).…”
Section: Iiv-6 As a Model To Study Antiviral Immunity Against Dna Virmentioning
confidence: 80%
See 2 more Smart Citations
“…In contrast to the sharp 21-nt peak in WT flies and AGO2 mutants, small RNAs in Dcr-2 mutants showed a broader size distribution, with only a minor enrichment at 21 nt. A similar shift toward small RNAs with sizes other than 21 nt was noted before in Dcr-2 mutant flies infected with vesicular stomatitis virus (14). Recombinant and immunoprecipitated Dicer-1 (Dcr-1) is able to process long dsRNA into siRNA in in vitro assays, albeit with low efficiency (39)(40)(41).…”
Section: Iiv-6 As a Model To Study Antiviral Immunity Against Dna Virmentioning
confidence: 80%
“…Indeed, early seminal work in mosquitoes and Drosophila cells directly detected viral small RNAs by Northern blot analysis and demonstrated that knockdown of core RNAi genes resulted in an increase in virus replication (8)(9)(10). In accordance, in the genetic model organism D. melanogaster, flies with defects in Dcr-2, R2D2, or AGO2 are unable to control RNA virus replication and, consequently, are hypersensitive to virus infection and succumb more rapidly than their wild-type (WT) controls (11)(12)(13)(14).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The monoclonal anti-dsRNA J2 antibody binds dsRNAs at least 40 bp long in a sequence-independent fashion (12)(13)(14). The J2 dsRNA monoclonal antibody was previously used to detect viral dsRNA by dsRNA immunoblotting, immunohistochemistry, ELISA, and immunoprecipitation in eukaryotic cells (13)(14)(15)(16)(17)(18)(19)(20). In this study, we used the J2 dsRNA antibody in an immunoprecipitation assay to enrich dsRNA from total RNA extracted from E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…A classical mechanism of this category is accomplished by IFN, a cytokine that is induced by dsRNA and creates an antiviral state in host cells (6)(7)(8). The third mechanism involves RNA interference (RNAi), by which the viral genome or transcripts are destroyed (9)(10)(11)(12). A newly discovered mechanism adopts autophagy for the elimination of intracellular virus (13)(14)(15).…”
mentioning
confidence: 99%